The performance comparison of artificial intelligence based distance relays for the protection of transmission lines - Muhammad Rameez Javed; Umar Siddique Virk; Aashir Waleed; Muhammad Yasir Jamal (Bulletin of Electrical Engineering and Informatics, 2022)
The safe and reliable generation and transmission of electricity is the desirable factor for utilities which arises the need of protection equipment such as relays in the power systems. According to recent studies, the conventional relays are not able to provide the required protection to the power systems, resulting in the emergence of various artificial intelligence (AI) techniques such as (i) artificial neural network (ANN); (ii) adaptive neuro fuzzy interface system (ANFIS); and (iii) fuzzy logic based relays for the protection. This work presents the protection scheme for transmission lines using various AI based distance relays along with performance comparison of these relays with a conventional numerical distance relay (NL). The comparison analysis has been performed by generating a test model in the MATLAB/Simulink environment and comparing “response time” against the same fault occurence for all relays. The comparison analysis found that AI based relays outperformed than conventional relay in terms of response time and accuracy level against the faults.